Primary Retroperitoneal Teratoma with Predominant Neurogenic Elements Masquerading as Adrenal Tumor - Sonam SHARMA; Leelavathi DAWSON; Ashish Kumar MANDAL (Türk Patoloji Dergisi, 2019)

(untitled)
Primary retroperitoneal teratomas are uncommon extragonadal nonseminomatous germ cell tumors that are composed of well differentiated parenchymal tissues which are derived from more than one of the three embryonic germ cell layers. Here we report an unusual and first of its kind, a case of primary mature cystic retroperitoneal teratoma mimicking as adrenal tumor in a 7-month-old female in which the tumor was predominantly composed of neurogenic tissue histologically which is unlike the usual pattern seen in the teratomas.